Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Project- Based Learning (PjBL) pada Materi Ekosistem Kelas X SMA 42 Jakarta: (Development of Project-Based Learning (PjBL)-Based Worksheets (WS) on Class X Ecosystem Materials of SMA Negeri 42 Jakarta) - Feby Riana; Sunarto; Jendri Mamangkey (Otus Edu Journal Prodi Tadris IPA Biologi UIN Mataram, 2024)
The student’s interest in learning needs to be encouraged through the presence of interactive, enjoyable teaching materials that help students achieve good learning outcomes and processes. Therefore, researchers innovatively developed Student Worksheets (LKPD) based on project- based learning (PjBL). The research aims to determine the feasibility of PjBL-based LKPD based on the assessment of experts (content, media, language) and student responses. The type of research used is Research and Development (R&D) with its ten working steps. The results of the expert assessment on the content of PjBL-based LKPD obtained a score of 82.03% “Very Feasible,” media experts 86.5% “Very Feasible,” and language experts 83% “Very Feasible,” as well as student responses of 53% “sufficiently positive.